Schellingova Clara - Škof, Lenart (Primerjalna književnost, 2017)
The paper deals with Schelling's dialogue Clara. Clara is among less frequently read and interpreted works of world philosophical literature. The aim of the paper is to reveal the inadequate thematization of love in western thought by putting to the fore the questions of femininity, the relationship between the living and the dead, and the connections we preserve with the departed through the "ontology of mourning." Clara proves to be one of the key philosophical/literary texts in terms of establishment and thematization of the "new ontology of love."
Keywords: "Clara"; Böhme, Jacob; death; filozofske interpretacije; filozofski roman; German philosophy; ljubezen; love; mourning; nemška filozofija; philosophical interpretations; philosophical novel; Schelling, Friedrich Wilhelm Joseph, 1775-1854; smrt; žalovanje